Effect of dietary fat source and bird’s sex on performance and peroxisome proliferator-activated receptor-γ gene expression in broiler chicks - BEHDANI, E; RAHMANI, H R; JAHANIAN, R (The Indian Journal of Animal Sciences, 2015)
The present study was conducted to investigate the effects of different sources and levels of dietary fat and bird’s sex on performance and gene expression of peroxisome proliferator-activated receptor-gamma (PPARγ), as an adipose differentiation and development regulatory key, in broiler chicks. One-week-old broiler chicks (840: 420 males and 420 females) were randomly allocated into a factorial arrangement of treatments including 3 different fat sources (soybean oil, yellow grease, and poultry fat), 3 different fat levels (0, 20, and 40 g/kg of diet), and 2 sex categories (male and female) based on a completely randomized design with 4 replicates of 15 birds each. In addition to performance parameters, abdominal fat tissue was collected from 6 wk-old chicks and total RNA was extracted by RNX reagent. A semi-quantitative reverse transcription PCR was performed to investigate the effects of dietary treatments on PPARγ gene expression. Results showed that dietary fat source had no effect on body weight gain (BWG); however, supplementation of 20 g/kg fat into the broiler diets improved feed conversion ratio (FCR). Male chicks had higher feed intake and BWG, as well as the better FCR values than female broilers. The highest expression of PPARγ gene was detected in the abdominal fat of birds fed on diets containing soybean oil and poultry fat, and females expressed PPARγ gene higher than males. Our findings indicated that different dietary fat sources and sex might affect the development of broiler abdominal fat by interfering in PPARγ gene expression.